1989
DOI: 10.1111/j.1365-2389.1989.tb01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenite fixation by soil particle‐size separates

Abstract: The fixation of selenite by clay-( < 2 pm), silt-(2-20 pm) and sand-size (20-2000 pm) separates from two arable soils was examined in solutions of 75Se-labelled sodium selenite using a Se/sample ratio of 1/106. Size separates were isolated by ultrasonic dispersion and gravity sedimentation. Selenite fixation was determined after equilibration periods ranging from 5 min to 26 h. Hydrogen peroxide-treated samples were included to examine the effect of organic matter on selenite fixation capacity.The relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Selenium, a non-metallic trace element occurring naturally in the environment, is an essential oligo-element for human beings and animals (Gissel-Nielsen et al, 1984;Burau, 1985;Christensen et al, 1989;Conde and Alaejos, 1997;Lemly, 2004). However, in large amounts, the toxicity of selenium compounds for animals, humans, wildlife and aquatic species has been evidenced (Burau, 1985;Conde and Alaejos, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Selenium, a non-metallic trace element occurring naturally in the environment, is an essential oligo-element for human beings and animals (Gissel-Nielsen et al, 1984;Burau, 1985;Christensen et al, 1989;Conde and Alaejos, 1997;Lemly, 2004). However, in large amounts, the toxicity of selenium compounds for animals, humans, wildlife and aquatic species has been evidenced (Burau, 1985;Conde and Alaejos, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…While selenite is strongly adsorbed to soil surfaces, selenate is much more weakly adsorbed (11)(12)(13). Studies on Se adsorption onto soils have indicated that the most important soil components are Fe-and Al-oxides and oxyhydroxides, Mn-oxides, clays, organic matter, and carbonates (11,(13)(14)(15). The levels of Se adsorption by Fe-and Mn-oxides are similar, with Al-oxides adsorbing slightly lower levels (16)(17)(18).…”
Section: Comparative Solubility and Sorption Of Different Se Speciesmentioning
confidence: 82%
“…Kaolinite adsorbs greater levels of selenite than montmorillonite below pH 6, even when the minerals have similar surface areas (13,19). Selenite adsorption is sometimes correlated with organic carbon in soils (14,15). However, negatively charged organic substances may also block adsorption sites, preventing Se adsorption (20,21).…”
Section: Comparative Solubility and Sorption Of Different Se Speciesmentioning
confidence: 96%
“…However, selenite, fluoride, and phosphate sorption mechanisms on real soils would be extremely complex and not fully revealed. Selenite sorption is influenced by the presence of organic matter (Christensen et al, 1989) and other anions (Brown and Carter, 1969), and also phosphate by organic substances (Moshi, 1974;Borggaard et al, 1990). Soil differs from pure systems in that the sites for ligand exchange reactions are not restricted to OH and water molecules (Pardo and Guadalix, 1990).…”
Section: Introductionmentioning
confidence: 99%